Progress of cGAS-STING signaling pathway-based modulation of immune response by traditional Chinese medicine in clinical diseases - Zhi, Hui; Fu, Hui; Zhang, Yunxin; Fan, Ni; Zhao, Chengcheng; Li, Yunfei; Sun, Yujiao; Li, Yingpeng (Frontiers in Immunology, 2024)
The cGAS-STING signaling pathway is a critical component of the innate immune response, playing a significant role in various diseases. As a central element of this pathway, STING responds to both endogenous and exogenous DNA stimuli, triggering the production of interferons and pro-inflammatory cytokines to enhance immune defenses against tumors and pathogens. However, dysregulated activation of the STING pathway is implicated in the pathogenesis of multiple diseases, including autoinflammation, viral infections, and cancer. Traditional Chinese Medicines (TCMs), which have a long history of use, have been associated with positive effects in disease prevention and treatment. TCM formulations (e.g., Lingguizhugan Decoction, Yi-Shen-Xie-Zhuo formula) and active compounds (e.g., Glabridin, Ginsenoside Rd) can modulate the cGAS-STING signaling pathway, thereby influencing the progression of inflammatory, infectious, or oncological diseases. This review explores the mechanisms by which TCMs interact with the cGAS-STING pathway to regulate immunity, focusing on their roles in infectious diseases, malignancies, and autoimmune disorders.